Order Thysanoptera Haliday, 1836. In: Zhang, Z.-Q. (Ed.) Animal Biodiversity: An Outline of Higher-level Classification and Survey of Taxonomic Richness (Addenda 2013) - Mound, Laurence A. (Zootaxa, 2013)
The world fauna of the insect Order Thysanoptera continues to be poorly sampled, with the tropical and subtropical areas of the southern continents inadequately surveyed (Mound 2014), and an almost complete lack of knowledge of the thrips fauna of New Guinea. In Australia, the number of described thrips species has increased from 400 to over 800 in 10 years, published largely in Zootaxa (Mound 2011a; Mound & Masumoto, 2005 & 2009; Mound & Tree, 2011). The number of described thrips species worldwide has increased 1.3% between 2011 (Mound 2011b) and 2013, and the other geographic areas responsible for this descriptive activity are China and South America. However, these numbers do not reflect the numbers of employed or experienced taxonomists, with the major international collections in Frankfurt, London, San Francisco and Washington no longer employing any thrips specialists.